Nonlinear Finite Element Analysis of Bone-Cement Interface Condition in Cemented Total Hip Replacement - Colombi, P.; Sgambi, L. (Engineering Transactions, 2015)
Loosening of cemented femoral hip component is one of the major failure mode in cemented total hip arthroplasty. The stern-cement and bone-cement interface conditions strongly influence the load transfer mechanism in the implant system and then the stress distribution in the bone, the stem and cement mantle. Nonlinear Coulomb friction model was often used in the literature to study the stem-cement interface. On the other hand, the bone-cement interface was usually considered to be bonded, and a tissue layer between the bone and the cement was introduced to model the long-term behaviour of a total hip arthroplasty. More recently, experimental investigations were carried out to study the general mechanical behaviour of the bone-cement interface under tensile or shear loading. Under tensile loading, the results showed that the post-yield tensile behaviour contributed substantially to the energy required to produce the failure of the bone-cement interface. Moreover the post-yield behaviour showed a positive correlation with the amount of interdigitation or bone density. The goal of this paper is to introduce a microstructural model based on a continuum damage mechanics for studying the bone-cement interface conditions. The present study is limited to the tensile behaviour since more detailed experimental data are available in this particular case. The numerical results show a good agreement with the experimental one and represent a first step toward the study of the bone-cement interface under combined normal and shear loading.